The Prevalence of Sleep Disorders and related risk factors in Flight Crews - KH Sadeghniiat Haghighi; Z Yazdi (طب کار)
Abstract Introduction:Excessive daytime sleepiness and other sleep disorders are receiving much attention as a cause of work accidents. Sleep disorders can disturb sleep and waking alertness. While the pilots and other flight crews suffer from sleep disorders, they will be unable to monitor airplane systems. This will reduce the safety of the flight. The aim of this study is assessment and analysis of prevalence,severity, and predictive factors of sleep disorders (insomnia, excessive daytime sleepiness) among flight crews. Methods:The sample was composed of 550 flight crews.Subjects were derived from a random sample of flight crews. They anonymously answered a questionnaire on their demographics, sleep habits, and work characteristics. Furthermore, they were asked to answer to standard questionnairesabout sleepiness and insomnia. Excessive daytime sleepiness was considered in them with indexes 10 or more in the ESS Results:Mean number of sleep hour per day was 6.8 ± 1.5 39% Slept lower than 6 hours. Other major findings were as follows: 56.1 % of the flight crews had difficulty in falling asleep, 41.6% Had difficulty in staying asleep, and 58.6% had problem with waking up too early. Overall, 45.5% were dissatisfied with sleep patterns and 51.9 % had an abnormal ISI (≥8). Conclusion: Our results showed a high prevalence of excessive daytime sleepiness, and insomnia in flight crews.